ANALISIS STRATEGI FUNGSIONAL DALAM PENGELOLAAN MEREK PROPERTI TERHADAP LOYALITAS PELANGGAN - Panjaitan, Lincoln; Purwoko, Bambang; Widyatama Sumarlin, Antonius (SEKOLAH PASCASARJANA PRESS, 2017)
The purpose of this research was to analyze the functional strategy in marketing mix management and brand management to customer loyalty. In this study used five variables, namely marketing mix, brand, marketing container, customer commitment and customer loyalty. The analysis technique used in this research by using Structural Equation Model (SEM). The data analyzed comes from the distribution of questionnaires to consumers by using accidental sampling technique at PT. Intiland, Tbk located in Tangerang area, which is Talaga Bestari. The results was obtained that there was a positive relationship between marketing mix and brand management on customer loyalty.